A population study on the time trend of cigarette smoking, cessation, and exposure to secondhand smoking from 2001 to 2013 in Taiwan. Issue 1 (December 2016) - Chiang, Chi-Yung; Chang, Hsing-Yi
Abstract Background In 2001, the National Health Interview Survey (NHIS) commenced in Taiwan. This survey, conducted on a sample of the whole Taiwanese population, is nationally representative and has a high response rate (>80 %). As a result, the four already completed surveys from 2001 to 2013 can be used to investigate the time trend of smoking prevalence, the rate of cessation, and exposure to secondhand smoking. Methods There were 72918 adults combined from the 2001, 2005, 2009 and 2013 National Health Interview Surveys (NHIS). Smoking status, exposure to secondhand smoking, and smoking cessation were asked, as well as demographic characteristics and other variables. Statistical analyses with sampling weights were carried out using SAS and SUDAAN. Results In males, the prevalence of smoking significantly decreased (rates in 4 surveys were 44.4 %, 44.6 %, 38.9 %, and 34.2 %, respectively). Since 2005 the rate of smoking cessation increased significantly (p = 0.033). The odd ratio (OR) exposure of secondhand among non-smokes (OR) in 2009 and 2013 were 0.96 (CI = 0.85–1.08) and 0.78 (CI = 0.70–0.88) comparing to 2005. In females, the prevalence of smoking was stable over time. The rate of smoking cessation only appeared significantly high in the older age group. The OR for exposure to secondhand smoking were 0.81 (CI = 0.74–0.89) and 0.68 (CI = 0.62–0.74), for 2009 and 2013 comparing to 2005, respectively. Conclusion Early anti-smoking legislation in Taiwan might have raised the awareness of the harm of smoking. However, the implementation of the Tobacco Hazards Prevention Act (THPA) in 2009 had great contribution to the reduction of smoking rate, especially in males.